ANALISIS STRATEGI INFLUENCER MARKETING PADA INSTAGRAM STUDIO DAPUR TAHUN 2024 - Yudhistira Akhmad Kurniawan; Widya Sastika (JURNAL LENTERA BISNIS, 2024)
Business competition has significantly increased over time as various companies introduce innovative flagship products. Consumers are more likely to choose well-known brands when selecting products. Therefore, companies must find effective marketing strategies to ensure that consumers recognize the products or services offered. One factor that can influence a company's or enterprise's recognition is improving brand awareness. To increase brand awareness,  one  of  the  most  appropriate  strategies  is  using  influencers  as  part  of promotions, or influencer marketing. Influencer  marketing involves promoting products through influencers to their followers. The purpose of this research is to understand the stages and implementation of influencer marketing at Studio Dapur. The method used in this research is descriptive qualitative, consisting of participatory observation, interviews, documentation, and triangulation. The results of this study conclude that the implementation of  the influencer  marketing  strategy on  Studio Dapur's  Instagram  has  yielded  positive results, particularly in terms of engagement rate, with an average achievement of 1-5% from the four influencers used. These results indicate strong performance and have a direct impact on increasing brand awareness.